2009
DOI: 10.1270/jsbbs.59.169
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effects of ion beam irradiation on rice

Abstract: We investigated the usefulness of ion beams for mutation breeding in rice (Oryza sativa L.) by comparing the efficiency (i.e., the ratio of desirable mutations to plant damage such as lethality and sterility), mutation rate, spectrum, and optimum dose to that of gamma rays. Rice seeds were irradiated with carbon ions (mean linear energy transfer = 76 and 107 keV/µm), helium ions (9 keV/µm), and gamma rays, and their survival and fertility were examined in the M 1 generation. The frequency of chlorophyll mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 17 publications
6
65
2
2
Order By: Relevance
“…Likewise, Abe et al (2002) discovered chlorophyll deficient mutants with albino, pale-green, yellow or stripped leave phenotypes in M 2 progeny of rice as a result of carbon ion irradiation. However, Yamaguchi et al (2009) reported that there were no differences in the spectrum of chlorophyll mutations between ion beams and γ rays, whereby, both high LET ion beam and low LET γ rays were found to induce albina, xantha, and other mutants such as striata (longitudinal white or yellow strips) and maculate (green or yellow spots distributed over the leaf) chlorophyll deficient mutants.…”
Section: Chlorophyll Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Abe et al (2002) discovered chlorophyll deficient mutants with albino, pale-green, yellow or stripped leave phenotypes in M 2 progeny of rice as a result of carbon ion irradiation. However, Yamaguchi et al (2009) reported that there were no differences in the spectrum of chlorophyll mutations between ion beams and γ rays, whereby, both high LET ion beam and low LET γ rays were found to induce albina, xantha, and other mutants such as striata (longitudinal white or yellow strips) and maculate (green or yellow spots distributed over the leaf) chlorophyll deficient mutants.…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…Recently, heavy ion beam irradiation has been established as an effective method of inducing mutations in many plant species due to its high frequency and broad spectrum (Hayashi et al, 2007). Ion beam irradiation is expected to result in different mutation induction effects and induction of novel mutations that have not been previously studied (Yamaguchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the lower dose of EMS was found to be more effective than gamma rays treatments (Table 1). Higher frequencies of chlorophyll mutation with lower doses of mutagen were reported in different crops by Yamaguchi et al, (2009) and Pawar et al, (2010). The decrease in chlorophyll mutation frequency at the highest doses of mutagen may be attributed to saturation in the mutational events which result in the elimination of the mutant cells during growth.…”
Section: Chlorophyll Mutantmentioning
confidence: 91%
“…선량의 구명이 필요하며 (Chontra et al, 2005;Misra et al, 2003;Sung et al, 2013), M 1 세대에서 적정 선량의 결정에는 생존율과 생장율이 주요 선발인자로 활용되고 있다 (Cvejic et al, 2011;Kang et al, 2013;Yamaguchi et al, 2009). 또한 방 사선을 조사한 식물은 M 1 세대에서는 구분키메라(sectorial chimera)이거나 열성일 경우가 많고 이형접합체(heterozygote) 에서는 표현형이 잘 나타나지 않기 때문에 동형접합(homozygosis) 이 일어나는 M 2 -M 3 세대에서 선발하는 것이 유리하다 (Shikazono et al, 1998;Yamaguchi et al, 2009).…”
unclassified